Perlindungan Hukum Karyawan yang di-PHK Akibat Mergernya Tokopedia dan Tiktok Shop dalam Perspektif Hukum Ketenagakerjaan - Latifah Ayu Lestari; Laeli Nikmatul Hidayah; Nurila Dwi Indriyati; Yandrianus Parsi Ema (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Mergers are generally conducted to improve operational efficiency, optimise the use of resources, and reduce costs. This research aims to examine the form of legal protection provided to employees who are laid off in normal situations and in special conditions such as company mergers or acquisitions. This research uses the normative juridical method to analyse labour regulations related to the merger process between Tokopedia and TikTokShop. This approach focuses on the study of legal norms contained in applicable laws and regulations. The result of this research is that the case of mass layoffs due to the merger of Tokopedia and TikTokShop shows that business practices that do not pay attention to social aspects can have a negative impact on workers' welfare and economic stability. In the event of layoffs due to mergers, companies are required to fulfil workers' rights in accordance with the provisions of the Labour Law, including severance pay and other rights.